A Series of Malignant Ovarian Cancers Arising From Within a Mature Cystic Teratoma. Issue 5 (June 2015) - Black, Jonathan D.; Roque, Dana M.; Pasternak, Monica C.; Buza, Natalia; Rutherford, Thomas J.; Schwartz, Peter E.; McCarthy, Shirley; Ratner, Elena
<x xml:space="preserve">Abstract</x> Background Mature cystic teratoma (MCT) is the most common germ cell tumor. It accounts for 10% to 20% of all ovarian masses. The likelihood of malignancy arising from within an MCT is low, and prognosis is poor. Methods A single-institution retrospective chart review was completed of all cases of MCT from 2004 to 2012. Multiple variables were examined including procedure performed, residual disease after surgery, surgical stage, histologic type, site of primary disease, date of recurrence, whether or not adjuvant chemotherapy was given, and whether or not there was death secondary to disease. Results During the study period, 1.2% of MCTs exhibited malignant transformation. The average age at presentation was 53.7 years. Mean follow-up time was 23 months. The most common presenting symptoms were bloating and abdominal pain. The average tumor size was 18 cm. Of note, 33% of cases were at least surgical stage IIIC at the time of presentation, whereas the remainder were stage IC or lower. Four (44.4%) of the 9 cases were identified as mucinous adenocarcinoma in addition to 1 case each of malignant melanoma, squamous cell carcinoma, and poorly differentiated adenocarcinoma. Only 1 patient experienced recurrence. One patient had a known MCT that was being managed expectantly and exhibited malignant transformation to a mucinous adenocarcinoma. Conclusions A large ovarian mass that is suspected to be a mature teratoma should be managed more aggressively in older patients. Our data suggest that although malignancy arising from mature teratomas is rare, it is more likely when patients are older than 40 years, the mass is greater than 18 cm, and there is any suspicion for a mucinous tumor. Like most ovarian tumors, these tumors most often present at later stages and, thus, can be difficult to treat. It is unclear what role chemotherapy or radiation plays in the management of these tumors.